Factors influencing quality decision‐making: regulatory and pharmaceutical industry perspectives. (28th January 2015) - Donelan, Ronan; Walker, Stuart; Salek, Sam
Abstract: Purpose: Currently, there is no qualified understanding of the influences, behaviours and other factors that impact the decision‐making of individuals and organisations involved in the development of new medicines. The aim of this qualitative study was to investigate and identify the important issues that influence quality decision‐making. Methods: Semi‐structured interviews were carried out with 29 senior decision‐makers from the pharmaceutical industry and regulatory authorities. The study participants were invited to discuss and review their perception of decision‐making within their organisation, its role in drug development and the regulatory review and their awareness and use of decision‐making techniques and the impact and monitoring of decisions. Results: The analyses (using NVivo 8 © software) resulted in the identification of 32 major and 97 sub‐themes that were consolidated into 19 overarching themes. These included items such as quality and validity of data, time considerations, organisational and cultural influences, analytical and logical approach, qualification and experience, subjective and personal considerations, political influences, precedents for similar previous decisions, understanding of the decision in question, impact analyses, audit trail, education and awareness, individual versus corporate decision‐making and frameworks. Relationships between themes were identified. The 19 overarching decision‐making themes were integrated into a framework for quality decision‐making. Conclusion: This study has achieved its aim of exploring decision‐making from the perspective of the individual and the organisation working in drug development and the regulatory review and has identified issues and considerations relating to making good quality decisions and allowed for the generation of a framework to aid quality decision‐making. Copyright © 2015 John Wiley & Sons, Ltd.